m6A Methylation Modification Patterns and Tumor Microenvironment Infiltration Characterization in Pancreatic Cancer - Sun, Mengyu; Xie, Meng; Zhang, Tongyue; Wang, Yijun; Huang, Wenjie; Xia, Limin (Frontiers in Immunology, 2021)
Recent studies have shown that RNA N6-methyladenosine (m6A) modification plays an important part in tumorigenesis and immune-related biological processes. However, the comprehensive landscape of immune cell infiltration characteristics in the tumor microenvironment (TME) mediated by m6A methylation modification in pancreatic cancer has not yet been elucidated. Based on consensus clustering algorithm, we identified two m6A modification subtypes and then determined two m6A-related gene subtypes among 434 pancreatic cancer samples. The TME characteristics of the identified gene subtypes were highly consistent with the immune-hot phenotype and the immune-cold phenotype respectively. According to the m6A score extracted from the m6A-related signature genes, patients can be divided into high and low m6A score groups. The low score group displayed a better prognosis and relatively strong immune infiltration. Further analysis showed that low m6A score correlated with lower tumor mutation burden and PD-L1 expression, and indicated a better response to immunotherapy. In general, m6A methylation modification is closely related to the diversity and complexity of immune infiltration in TME. Evaluating the m6A modification pattern and immune infiltration characteristics of individual tumors can help deepen our understanding of the tumor microenvironment landscape and promote a more effective clinical practice of immunotherapy.